Psycho-Semantic Methods in the Study of the Phenomenon of Loneliness - Zh V Puzanova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2011)
In the article the author continues to introduce the reader to the findings of the exploratory research aimed to reconstruct some structural elements of the phenomenon of loneliness. In this instance, the article describes the application of psycho-semantic methods used in combination with the method of unfinished sentences. The approach used in the article enables the author to study loneliness turning directly to the affective level of the respondents' emotions.